An enzyme-mediated bioorthogonal labeling method for genome-wide mapping of 5-hydroxymethyluracil. Issue 42 (12th October 2021) - Ma, Cheng-Jie; Li, Lin; Shao, Wen-Xuan; Ding, Jiang-Hui; Cai, Xiao-Li; Lun, Zhao-Rong; Yuan, Bi-Feng; Feng, Yu-Qi
Abstract : We developed an enzyme-mediated bioorthogonal labeling strategy for the enrichment and genome-wide mapping of 5hmU. With this strategy, we provided the first map of 5hmU in the whole Trypanosoma brucei genome. Abstract : DNA 5-hydroxymethyluracil (5hmU) is a thymine modification existing in the genomes of various organisms. The post-replicative formation of 5hmU occurs via hydroxylation of thymine by ten-eleven translocation (TET) dioxygenases in mammals and J-binding proteins (JBPs) in protozoans, respectively. In addition, 5hmU can also be generated through oxidation of thymine by reactive oxygen species or deamination of 5hmC by cytidine deaminase. While the biological roles of 5hmU have not yet been fully explored, determining its genomic location will highly assist in elucidating its functions. Herein, we report a novel enzyme-mediated bioorthogonal labeling method for selective enrichment of 5hmU in genomes. 5hmU DNA kinase (5hmUDK) was utilized to selectively install an azide (N3 ) group or alkynyl group into the hydroxyl moiety of 5hmU followed by incorporation of the biotin linker through click chemistry, which enabled the capture of 5hmU-containing DNA fragments via streptavidin pull-down. The enriched fragments were applied to deep sequencing to determine the genomic distribution of 5hmU. With this established enzyme-mediated bioorthogonal labeling strategy, we achieved the genome-wide mapping of 5hmU in Trypanosoma brucei . The method described here will allow for a better understanding of the functional roles and dynamics of 5hmU in genomes.